2018
DOI: 10.3390/v10110639
|View full text |Cite
|
Sign up to set email alerts
|

Human Bocavirus Infection Markers in Peripheral Blood and Stool Samples of Children with Acute Gastroenteritis

Abstract: Human bocaviruses (HBoVs) 1–4 belong to the Parvoviridae family, and they infect the respiratory or gastrointestinal tracts in children. We investigated the prevalence of HBoV1–4 DNAs in the blood and stool samples, and of HBoV1–4 IgG and IgM in the plasma samples, of children presenting with acute gastroenteritis (AGE). In addition, we identified HBoV co-infections with the five most frequent gastrointestinal pathogens. A total of 83 paired blood and stool samples were collected from children aged five years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
1
13
0
1
Order By: Relevance
“…In Taiwan, the dominant HBoV species associated with AGE is HBoV1, followed by HBoV2. Similar results have also been observed in the United States [25], India [26], Thailand [5], Latvia [9], and Bangladesh [27]. However, HBoV2 is the dominant species in some countries such as China [28], Nigeria and Tunisia [2], Australia [4], Russia [29], and Turkey [27].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In Taiwan, the dominant HBoV species associated with AGE is HBoV1, followed by HBoV2. Similar results have also been observed in the United States [25], India [26], Thailand [5], Latvia [9], and Bangladesh [27]. However, HBoV2 is the dominant species in some countries such as China [28], Nigeria and Tunisia [2], Australia [4], Russia [29], and Turkey [27].…”
Section: Discussionsupporting
confidence: 79%
“…HBoVs cause a variety of clinical symptoms and can be isolated from several types of specimens that include nasopharyngeal aspirates, fecal, blood, and cerebrospinal fluid [4][5][6][7][8][9]. HBoV1 is most commonly detected from respiratory specimens, while HBoV2-4 is often detected in fecal specimens [4][5][6]10].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenetic role and clinical implications of human parvoviruses are addressed in two studies presented in this collection, about the role of human bocaviruses and parvovirus B19. In an observational study [18], a significant association of human bocaviruses to gastroenteritis is reported, thus further expanding their clinical involvement in addition to the established association with respiratory tract infections. In a systematic review and meta-analysis study [19], the significance of the detection of parvovirus B19 genomes in endomyocardial biopsies of patients presenting with myocarditis or dilated cardiomyopathy is discussed.…”
Section: The Articles In the Special Issuementioning
confidence: 99%
“…Caliciviridae, Dicistroviridae, Iflaviridae, Marnaviridae, Picornaviridae, Polycipiviridae, Secoviridae and Solinviviridae [3,4] are classified into eight recognized families in this order. Most viruses of this order are capable of infecting a wide range of hosts, including invertebrates, vertebrates, plants, fungi, and algae, and of causing a variety of host clinical conditions, including the common cold, acute diarrhea, heart disease, liver disease, and extreme neuropathy [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Posa-like viruses (posavirus = porcine stool-associated RNA viruses), a group of Picornavirales consisting of divergent viruses that share a similar genome architecture, have been found predominantly in fecal samples in a wide range of hosts [4,6,8,9,[13][14][15][16][17][18]. In pigs and water barns obtained from swine farms, posaviruses were detected by NGS [15,16,19], fish stoolassociated RNA virus (fisavirus) was identified in the intestinal content of carps [17], and human stool-associated RNA virus (husavirus) was identified in primarily stable human feces [10].…”
Section: Introductionmentioning
confidence: 99%